Win-At-All-Costs? Exploring Bottom-line Mentality as a Buffer between Athletic Director Servant Leadership and Coach Commitment - Matt Robinson; Jun Woo Kim; Marshall Magnusen; Mitchell Neubert (Journal of Applied Sports Management, 2021)
Servant leadership (SL), characterized by enduring qualities of genuine caring, humility, and empathy, has been positively associated with numerous leader effectiveness outcomes (e.g., employee satisfaction) across sport and non-sport settings. This study addresses the need to more thoroughly investigate follower characteristics that may allow servant leadership to be more (or less) effective in a sport context. Drawing from leader-member exchange theory, this study predicted head coach bottom-line mentality (i.e. 1-dimensional, win-at-all-costs attitude) would negatively impact the relationship between athletic director SL and head coach commitment. Surveying a sample of 810 interscholastic HCs across the USA, Structural Equation Modeling revealed SL’s positive effect on head coach commitment. Analysis also revealed the interaction of SL and bottom-line mentality had a significant negative impact on commitment. Thus, when follower bottom-line mentality is win-at-all-costs, the positive influence of SL appears to be diminished.
Keywords: Attitude; High School; Interscholastic Sport; Leader; Management; Organizational Behavior